Emotion dysregulation in insomnia disorder: the possible role of psychiatric comorbidity - Jansson-Fröjmark, Markus; Hossain, Samiul (Frontiers in Sleep, 2024)
The purpose with of this study was to investigate the link between emotion dysregulation and insomnia disorder as well as the impact possible role of psychiatric comorbidity on the association. More specifically, the aim was to examine whether the elevations in emotion dysregulation in insomnia are dependent on co-occurring psychiatric comorbidity, in this study defined as anxiety disorders and/or major depression.Methods: Four diagnostically differing groups with 25 participants in each were recruited: normal sleep, normal sleep with psychiatric comorbidity (anxiety disorders and major depression), insomnia disorder, and insomnia disorder with psychiatric comorbidity. The 100 study participants completed self-report scales and items assessing socio-demographic parameters, symptoms of insomnia, anxiety, and depression, generic emotion regulation, and insomnia-specific emotion regulation.Results: Concerning generic emotion regulation, the results showed that psychiatric comorbidity, but not insomnia, was associated with elevations in generic emotion dysregulation. Psychiatric comorbidity was distinctly related to elevations in non-acceptance, goals, and impulse domains (d = 1.09-1.22). Regarding insomnia-specific emotion regulation, the findings demonstrated that insomnia, with or without psychiatric comorbidity, was related to heightened use of insomnia-associated emotion dysregulation strategies. More specifically, iInsomnia was uniquely associated with elevated unhelpful beliefs about sleep and safety behaviors (d = 1.00-1.04).The current findings support the notion that insomnia is associated with specific, but not generic, emotion dysregulation strategies. These results have relevance for the conceptualization of the role of emotion dysregulation in insomnia and the clinical management of insomnia.